KEMAMPUAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SD ISLAM TERPADU WAHDAH ISLAMIYAH SULAWESI SELATAN - Tengku Moh Hasbih (UNISAN JURNAL, 2024)
A nation will advance in the event that it has a well-rounded schooling, well-rounded schooling can happen on the off chance that the educators have great skill too. A teacher or educator plays a vital part in molding the person and persuading understudies’ advantage in learning, so working on the capacity or skill of the teacher is vital. Scientists utilized subjective exploration strategies. The priSekolah Dasarry information sources in this study were the Sekolah Chiefs, Educators, and Understudies, while the auxiliary information sources came from Sekolah Dasar drasa managerial records. Information assortment procedures Specialists utilized perception, meetings and documentation. For information approval, the analyst utilized triangulation method. The consequences of this investigation discovered that the Sekolah Dasarnagement of the in carrying out the Sekolah Dasarnagement elements of arranging, sorting out, preparing and regulating had been done well, including Sekolah Dasarking movement plans and their spending plans, coordinating: isolating undertakings to their subordinates, faculty about their obligations and obligations, preparing: persuading and giving prizes and punishSekolah Dasarn as a prize and repriSekolah Dasarnd for the consequences of educator perforSekolah Dasarnce, and oversight: direct management and assessment in movements of every sort toward the start of execution, during execution and after finish of exercises. The Sekolah Dasarnagement of the Sekolah Chief has had the option to optiSekolah Dasarlly work on the ability of educators at Sekolah Dasar Islam Terpadu Wahdah Islamiyah , specifically friendly skill and character capability, however not exactly optiSekolah Dasarl in working on academic skill and expert capability.